Correspondence on "Cyanine Dyes Containing Quinoline Moieties: History, Synthesis, Optical Properties and Applications". Issue 23 (5th April 2022) - Mustroph, Heinz
Abstract: In the review on "Cyanine Dyes Containing Quinoline Moieties: History, Synthesis, Optical Properties and Applications" (K. Ilina, M. Henary, Chem Eur. J . 2021, 27, 2430; https://doi.org/10.1002/chem.202003697 ), some essential aspects were incorrectly described and discussed. To avoid further confusion, this correspondence tries to clarify both the structures and the history of some cyanine and apocyanine dyes that were not presented sufficiently. Abstract : Reviews are more important today than ever . With the glut of new publications, it has become increasing difficult to read all original papers in detail. So, scientists usually first get an overview from reviews. In the review on "Cyanine Dyes Containing Quinoline Moieties: History, Synthesis, Optical Properties and Applications" ( Chem Eur. J . 2021, 27, 2430), some aspects were incorrectly described and discussed. This correspondence tries to clarify some basics that have been presented insufficiently in the review.